(untitled) (Revista Brasileira Multidisciplinar, 2020)
The fishing activity is considered as a fundamentally male practice. In fishing communities, there is a social division of labor by gender and many women survive from other fishing modalities. This study concerns the fishing community of Nzeto (Zaire province, Angola), where artisanal fishing is traditionally a subsistence activity and aims to discuss the sociopolitical framing of gender in fishing activities, searching the relationship between fisherwomen and the environment. In order to understand the fishing community and the observed co-op, as well as its workers, we asked 18 fisherwomen to answer the survey, 12 of them being from the co-op plus 6 who were not. We intended to divide them categorically aiming to establish a comparative study between fisherwomen who are integrated into an organization that defends their varied interests and those who exercise their profession without any support of institutional recognition. We verify that the integration of women in artisanal fishing is only accomplished thanks to their own initiative and efforts. Women take on the responsibility of transporting, stocking, and drying the fish, and also saling it. Besides, they also demand the construction of a facility where they can take shelter from direct exposure to sunlight and rain.They work under poor sanitary conditions, and handling the catch lacks better hygiene conditions. There are no choices but increasing the family income, even under hard and painful work conditions. From the cultural perspective, women taking control of the fishing process results in stigma´ rupture that attempts to exclude them from the productive circuit.